An Alaskan twin surprise - Calhoune, Belle (Love inspired., 2020)
"The last person Gabriel Lawson expects to find in town is Rachel Marshall--especially with twin toddlers in tow. Gabriel refuses to risk his heart again on the woman who left him at the altar years ago. But working to renovate her mother's house means he must spend time with Rachel and her adorable twins...and soon he can't help but wish they were his family." -- Page [4] cover.